PSYCHOMETRIC PROPERTIES OF THE GROUP ENVIRONMENT QUESTIONNAIRE (GEQ) FOR THE HIGH PERFORMANCE SOCCER AND FUTSAL CONTEXT - José Roberto Andrade do Nascimento Junior; Andressa Ribeiro Contreira; Caio Rosas Moreira; Gislaine Contessoto Pizzo; Vandresa Teixeira Ribeiro; Lenamar Fiorese Vieira (Journal of Physical Education)
ABSTRACT This study aimed at analyzing the psychometric proprieties of the Brazilian version of the Group Environment Questionnaire (GEQ) in futsal and soccer high performance contexts. The sample consisted of 441 male athletes, 140 soccer players and 301 futsal players. The data analysis was carried out by using the following tests: Cronbach's alpha (α), Composite Reliability (CR), Confirmatory Factor Analysis (CFA), Average Variance Extracted (AVE) and Spearman's correlation. The results showed that the GEQ has a good internal consistency (α>0,70/CC>0,70). The CFA revealed that the model (M2) with 16 items showed an adequate fit for soccer and futsal athletes, and that the multigroup analysis supported a partial invariance (metric and configurational ones) among soccer and futsal players. The GEQ had a good external validity (r>0,50/p<0,05) with all the CART-Q dimensions (Coach-Athlete Relationship Questionnaire - athlete version). It was concluded that the GEQ version showed good psychometric properties in Brazilian high performance soccer and futsal contexts.